General questions of the module of special pedagogy: categories of children in need of special support. - G`aniyeva Dildora Muqimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
There was a need to clearly define the place of defectology in the system of sciences, namely in the structure of pedagogy. Development of contacts with the world scientific community and foreign pedagogical practice since the beginning of the 90s. clearly showed "diagnostic" in the context of the humanistic paradigm.